The Critical Sense of "experience in general" - Matteucci, Giovanni (Aesthetica Preprint, 2022)
The essay examines an implication that originates from Garroni’s innovative invitation to expand the jurisdiction of aesthetics from art to “experience in general”. This thesis, in the terms used by Garroni, renders the meaning of “aesthetic” merely occasional. The essay aims at showing a way of welcoming the invitation to consider aesthetics as a non-disciplinary modality of theoretical research, while still conferring a pregnant meaning upon the aesthetic component of experience. Exemplary in this regard is the comparison between Kantian and Deweyan strategies to describe the experiential character of the aesthetic.